The Twenty-Ninth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2010)

The Thirtieth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2011)

The Thirty-First Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2012)

The Thirty-Second Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2013)

The Thirty-Third Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2014)

The Thirty-Fourth Annual Report - The English Speaking Catholic Council (ESCC) (English Speaking Catholic Council, 2015)

The English Speaking Catholic Council: The Thirty-Fifth Annual Report - The English Speaking Catholic Council (ESCC) (2016)

2016-17 Annual Report - The English Speaking Catholic Council (ESCC) (2017)

Annual Report 2017-18 - The English Speaking Catholic Council (ESCC) (2018)

Annual Report 2018-19 - The English Speaking Catholic Council (ESCC) (2019)

Strategic Plan : 2011-2016 - The English Speaking Catholic Council (ESCC) (2010)

Brief : Submitted to the Federal Parliamentary Committee on Palliative and Compassionate Care by the English-speaking Catholic Council - The English Speaking Catholic Council (ESCC) (2010)
The English Speaking Catholic Council acknowledges with deep gratitude the invaluable contribution of the principal authors of this brief: Dr. Ramona Coelho, a family physician who works at CLSC Metro in Montreal. Her training included a focus in palliative care. She spends half of her practice caring for disabled and frail elderly persons who are homebound. And Daniel Cere, Ph.D., Professor, Faculty of Religious Studies, McGill University, and member of the Board of the ESCC. The English Speaking Catholic Council is pleased to present this Brief to the Federal Parliamentary Committee on Palliative and Compassionate Care.

Directives on Daycares - The English Speaking Catholic Council (ESCC) (2011)

Statement Regarding the Situation of the Catholic Times - The English Speaking Catholic Council (ESCC) (2010)

Statement on Bill 40 : An Act to Amend the Education Act Principally with Respect to School Organization and Governance - The English Speaking Catholic Council (ESCC) (2019)

General Consultation and Public Hearings on Bill 60 - The English Speaking Catholic Council (ESCC) (2013)
The English Speaking Catholic Council (ESCC) objects to the proposed “Charter,” Bill 60, on the following grounds: • It threatens to erode the historically and legislatively foundational freedoms of conscience, religion, opinion and expression. These are considered to be “first” freedoms in our society and any trend to dilute or undermine these freedoms must be resisted. • It proposes a secularized society in which religious expression and practice are marginalized. It seeks to reframe the public discussion so that the exercising of Charter-protected rights is to be understood as an imposition upon society which requires the permission of the State. • It muddies the separation of Church and State as it proposes the State has the power to define the nature of religious belief, practice and expression. • In all of the aforementioned points the role of the State is elevated above the proper parameters of a democratically elected and responsible government. The ESCC calls upon the Government of Quebec to withdraw Bill 60.

[Carter Statement] - The English Speaking Catholic Council (ESCC) (2015)

Submitted to the Select Committee on Dying with Dignity - The English Speaking Catholic Council (ESCC) (2010)
In 1980, a group of individuals who represented various sectors of the English-speaking Catholic community and its organizations met with the idea of consolidating our human and material resources for the development of our community. This led to the formation in 1981 of the English Speaking Catholic Council (ESCC) with a mandate to act as a focal point in coordinating the English-speaking Catholic community of Greater Montreal. Over the years, the ESCC has assumed a higher profile which now extends throughout the Province and beyond. Inspired by the contemporary Catholic understanding of the role of the laity in the modern world, the English Speaking Catholic Council assists in the promotion of its community’s values and advocates those values in the resolution of issues affecting this community. The Board of Directors is made up of women and men from both the private and public sectors, all volunteers, who come together with a commitment to support their community in education, health and social services, community animation, culture and social justice.